Dispersão de nanotubos de carbono e nanocristais de celulose em diferentes quitosanas: estudo das suspensões e propriedades de nanocompósitos poliméricos - Sandra Aparecida Alexandre (2015)
In this study different suspensions were prepared by dispersing functionalized carbon nanotubes (MWCNT) and/or cellulose nanocrystals (NCC) in acidic solutions of low ( = 3,3x104 g/mol and = 25%) and high molar mass ( = 3,7x105 g/mol and = 31%) chitosans andglycerol (10% by weight) with the use of a tip ultrasound. The dispersions were characterized in order to find what concentration of each nanofiller would be possible to disperse with those chitosans without the use of further centrifugation steps. It was found that concentrations of NCC ofabout 10wt% and 1w% and nanotubes in the order of 2wt% and 0.5wt% were effectively dispersed in such matrices (high and low molecular weights, respectively) and the suspensions remain stableeven after 3 months or more (at rest), indicating the filler stabilization by the chitosan with the preparation of thermodynamic dispersions. From these suspensions, binary (CHI /MWCNT or NCC) and ternary (CHI/MWCNT/NCC) polymer nanocomposites were prepared by casting technique. The addition of MWCNTs and NCCs affects the thermal stability of the chitosan (as measured by thermogravimetry), indicating possible interaction between the filler and matrix. Infrared spectroscopy data of the composite films showed the interaction filler/chitosan, which was corroborated by the scanning and transmission electronic microscopies images. These images showed good adhesion of the fillers to the polymer matrix as a result of MWCNT/CHI, NCC/CHI and CHI/MWCNT/NCC interactions. Furthermore, another evidence of this interaction (obtained in the fracture images) is the fact that no nanotube was pulled out from the matrix with the fracture, as well the observation of curved nanotubes connecting "points"of the fractured surface. This morphology is essential to the transfer of tension between the fillers and matrix when the material is subjected to mechanical stress. In fact, the mechanical tests showed that both the nanotubes (in a smaller scale) and NCC are excellent reinforcement for chitosan. Increases were observed in properties such as modulus, tensile strength, elongation at break and toughness. Moreover, in the ternary composite, the synergy between the matrix, nanocrystals and nanotubes allowed the preparation of nanocomposites with superior properties to those found in the binary systems using low concentrations of the nanofiller, especially in the high molecular weight chitosan matrix.